2012
DOI: 10.1117/1.jbo.17.10.106004
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency oscillations measured in the periphery with near-infrared spectroscopy are strongly correlated with blood oxygen level-dependent functional magnetic resonance imaging signals

Abstract: Abstract. Low-frequency oscillations (LFOs) in the range of 0.01-0.15 Hz are commonly observed in functional imaging studies, such as blood oxygen level-dependent functional magnetic resonance imaging (BOLD fMRI) and functional near-infrared spectroscopy (fNIRS). Some of these LFOs are nonneuronal and are closely related to autonomic physiological processes. In the current study, we conducted a concurrent resting-state fMRI and NIRS experiment with healthy volunteers. LFO data was collected simultaneously at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 45 publications
10
103
0
Order By: Relevance
“…Spontaneous hemodynamic oscillation in the resting brain has previously been detected not only with NIRS 31-34 but also with blood oxygen level-dependent functional MRI (fMRI). [35][36][37][38][39] Although the origin and function of the spontaneous oscillation remain unclear, two possibilities have been proposed. First, a part of the spontaneous oscillations in the brain could originate from the global circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous hemodynamic oscillation in the resting brain has previously been detected not only with NIRS 31-34 but also with blood oxygen level-dependent functional MRI (fMRI). [35][36][37][38][39] Although the origin and function of the spontaneous oscillation remain unclear, two possibilities have been proposed. First, a part of the spontaneous oscillations in the brain could originate from the global circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The second possibility is that the spontaneous oscillation of oxy-Hb might reflect resting state neural activity. 29,31,[35][36][37][38][39] In NIRS activation studies, changes of oxy-Hb during activation imply evoked changes of rCBF in response to neuronal activation, since changes in oxy-Hb are correlated with changes in rCBF. 10 In addition, simultaneous measurements of NIRS and EEG at rest demonstrated a relationship between oxy-Hb change and mean EEG peak frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the hemodynamic parameters HbO 2 and Hb oscillating at 0.01 to 0.15 Hz are believed to be closely related to brain activation. 16 The A5 component (<0.15 Hz) was used to extract the relative concentration changes of HbO 2 , Hb, and total hemoglobin (HbT; HbT ¼ HbO 2 þ Hb). The 10 s data prior to anesthesia induction were used as the baseline during the calculation of relative HbO 2 and Hb (using MBLL).…”
Section: Data Preprocessingmentioning
confidence: 99%
“…fNIRS supplies a safe, nonionizing radiative, noninvasive, and cost-effective measurement of cerebral hemodynamic changes in cerebral cortex in comparison with positron emission tomography (PET) and functional magnetic resonance imaging (fMRI). 16,17 Over the years, this technique has evolved into a versatile medical diagnostic modality and has been used to investigate many brain functions. [18][19][20][21][22][23] In general, there are three types of fNIRS systems: continuous wave (CW) modality, frequency-domain (FD) modality, and time-domain modality.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that blood in the body is sensitive to a magnetic field coming from a particular direction, [152] [153], Iron in heme appears to have anisotropic (directionally sensitive) qualities at room temperature, [154], paramagnetic neurotransmitters are concentrated in the mesencephalon, (used by the body for reward and addiction) [155].…”
Section: Directional Sensitivitymentioning
confidence: 99%